Echoes of Hylas and the Poetics of Allusion in Propertius - Mariapia Pietropaolo (Parole Rubate, 2012)
For Propertius the myth of Hylas exemplifies a poetics of selective appropriation and transformation by means of echoes and allusions. He brings it into his poetry as an exemplum, both erotic and metapoetic, and offers evidence that his penchant for echoes and allusions is essentially the result of a Hylan poetics of elegy. By using the echoic mode of composition inherent in the myth of Hylas, Propertius illustrates the principle that elegiac poetry is grounded in a complex dialogue of intertextual and intratextual allusion and citations.